Romania : Selected Issues and Statistical Appendix. (IMF Staff Country Reports; Country Report ;, 2004)
This Selected Issues paper for Romania reports that the practice of nonpayment and arrears accumulation has been widespread in Romania. Managers of enterprises that remain in the pipeline for privatization for long periods of time have little incentive to reduce arrears. The state contributed to growth of arrears by accepting nonmonetary tax and utility payments, using tax offsets in procurement, and tolerating payment arrears. These practices have been prevalent at all levels of state and local government, as well as state utility companies.